2021
DOI: 10.3390/w13111472
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Extremes and Responses to Climate Change in the Kelantan River Basin, Malaysia, Based on the CMIP6 HighResMIP Experiments

Abstract: This study introduces a hydro-climatic extremes assessment framework that combines the latest climate simulations from the Coupled Model Intercomparison Project Phase 6 (CMIP6) HighResMIP with the Soil and Water Assessment (SWAT) model, and examines the influence of the different climate model resolutions. Sixty-six hydrological and environmental flow indicators from the Indicators of Hydrologic Alteration (IHA) were computed to assess future extreme flows in the Kelantan River Basin (KRB), Malaysia, which is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The same method is used to replace the missing data in the MMD precipitation observation with the interpolated values based on the available data of the time step, though most of the applied MMD observations are from the principal climate stations of the WMO which are well maintained and thus contain fewer missing values than other stations (Tan et al 2021). The inter-comparison of the full-year precipitation amount and those during the southwest monsoon (MJJA) and northeast monsoon (NDJF) seasons is made for the observed precipitation data and the GCM simulations.…”
Section: Methods For Model Validationmentioning
confidence: 99%
“…The same method is used to replace the missing data in the MMD precipitation observation with the interpolated values based on the available data of the time step, though most of the applied MMD observations are from the principal climate stations of the WMO which are well maintained and thus contain fewer missing values than other stations (Tan et al 2021). The inter-comparison of the full-year precipitation amount and those during the southwest monsoon (MJJA) and northeast monsoon (NDJF) seasons is made for the observed precipitation data and the GCM simulations.…”
Section: Methods For Model Validationmentioning
confidence: 99%
“…Since original climate models even contain biases in high-resolution versions, a bias correction scheme should be implemented before applying them to regional-or local-scale studies. The quantile mapping approach adopted by Tan et al [41] to bias correct the CMIP6 HighResMIP models in the Kelantan River Basin, Malaysia, was used in this study. We found that the quantile mapping approach can effectively correct the occurrence period of peak monthly precipitation in December and precipitation amount for all months.…”
Section: Climate Change Scenariosmentioning
confidence: 99%
“…The ability to resolve small scale weather features is important for basin scale analysis, and means HighResMIP GCMs will likely be employed by hydrologists to study hydro-climatic changes around the world, including the tropical regions. Tan, et al [20] found that high-resolution HighResMIP models projected a higher flow rate during flood season than low-resolution models in the Kelantan River Basin, Malaysia. To date, there has been little investigation of about the role of HighResMIP models resolution on hydro-climatic projections.…”
Section: Introductionmentioning
confidence: 99%